A psychologically informed, audiologist-delivered, manualised intervention for tinnitus: protocol for a randomised controlled feasibility trial (Tin Man study) - Taylor, John; Hall, Deborah A.; Walker, Dawn-Marie; McMurran, Mary; Casey, Amanda; Stockdale, David; Featherstone, Debbie; Thompson, Dean M; MacDonald, Carol; Hoare, Derek J. (Biomed Central, 2017)
Background